(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The emergence and spread of carbapenem-hydrolysing beta-lactamases among Enterobacteriaceae and Non-fermentative Gram-negative bacilli organisms like Pseudomonas spp. or Acinetobacter baumannii over the past ten years is a serious problem in hospital settings. This problem has been exacerbated by the fact that carbapenems are no longer as effective against these pathogens. Aside from that, numerous bacteria in the natural environment form biofilms. When opportunistic biofilm-forming pathogens cause infections, they can cause severe symptoms in many cases and death in people who don't have strong immune systems. No new class of antibiotic have been reported in the last several decades. In this context, Recent years have seen a rise in the importance of nanobiotechnology in the production of nanomaterials that function as antibacterial agents. It is possible for nanoparticles to be active molecules or compounds that react with bacterial cells to kill them. This has the potential to resolve issues associated with multidrug resistance and inhibit biofilm. In the present study, synthesized ZnO nanoflakes were utilized. These nanoflakes had an average crystallite size of 21.5 ± 4.8 nm, a thickness of 20-50 nm, and different characteristics. We have included 67 Carbapenem resistant Enterobacteriaceae (CRE) and Non-fermentative Gram-negative bacilli isolates, which were isolated from various clinical samples. ZnO-NPs showed strong antibacterial and antibiofilm action against clinical isolates, according to growth kinetics and antibiofilm assay. In addition, we looked into how ZnO-NPs interact with clinical bacterial strains to determine their mode of action. ZnO is thought to exert its effects via reactive oxygen species (ROS) production, which boosts membrane lipid peroxidation and ultimately results in the loss of reducing sugars through membrane leakage. These findings suggest that in future ZnO-NPs might be an effective alternate treatment of choice to treat infections caused by CR bacterial isolates.